Adenosine A2A receptor agonist prevents cardiac remodeling and dysfunction in spontaneously hypertensive male rats after myocardial infarction - da Silva JS; Gabriel-Costa D; Sudo RT; Wang H; Groban L; Ferraz EB; Nascimento JHM; Fraga CAM; Barreiro EJ; Zapata-Sudo G (Dove Medical Press, 2017)
Jaqueline S da Silva,1 Daniele Gabriel-Costa,1 Roberto T Sudo,1 Hao Wang,2 Leanne Groban,2 Emanuele B Ferraz,3 José Hamilton M Nascimento,3 Carlos Alberto M Fraga,1 Eliezer J Barreiro,1 Gisele Zapata-Sudo1 1Research Program Development of Drugs, Institute of Biomedical Sciences, Universidade Federal do Rio de Janeiro, Rio de Janeiro, Brazil; 2Department of Anesthesiology, Wake Forest School of Medicine, Winston-Salem, NC, USA; 3Institute of Biophysics Carlos Chagas Filho, Universidade Federal do Rio de Janeiro, Rio de Janeiro, Brazil Background: This work evaluated the hypothesis that 3,4-methylenedioxybenzoyl-2- thienylhydrazone (LASSBio-294), an agonist of adenosine A2A  receptor, could be beneficial for preventing cardiac dysfunction due to hypertension associated with myocardial infarction (MI). Methods: Male spontaneously hypertensive rats (SHR) were randomly divided into four groups (six animals per group): sham-operation (SHR-Sham), and myocardial infarction rats (SHR-MI) were treated orally either with vehicle or LASSBio-294 (10 and 20 mg.kg-1.d-1) for 4 weeks. Echocardiography and in vivo hemodynamic parameters measured left ventricle (LV) structure and function. Exercise tolerance was evaluated using a treadmill test. Cardiac remodeling was accessed by LV collagen deposition and tumor necrosis factor α expression. Results: Early mitral inflow velocity was significantly reduced in the SHR-MI group, and there was significant recovery in a dose-dependent manner after treatment with LASSBio-294. Exercise intolerance observed in the SHR-MI group was prevented by 10 mg.kg-1.d-1 of LASSBio-294, and exercise tolerance exceeded that of the SHR-Sham group at 20 mg.kg-1.d-1. LV end-diastolic pressure increased after MI, and this was prevented by 10 and 20 mg.kg-1.d-1 of LASSBio-294. Sarcoplasmic reticulum Ca2+ ATPase levels were restored in a dose-dependent manner after treatment with LASSBio-294. Fibrosis and inflammatory processes were also counteracted by LASSBio-294, with reductions in LV collagen deposition and tumor necrosis factor α expression. Conclusion: In summary, oral administration of LASSBio-294 after MI in a dose-dependent manner prevented the development of cardiac dysfunction, demonstrating this compound’s potential as an alternative treatment for heart failure in the setting of ischemic heart disease with superimposed chronic hypertension. Keywords: hypertension, myocardial infarction, LASSBio-294 and agonist of adenosine receptor A2A